2009
DOI: 10.1007/s00467-008-0931-x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre prospective randomised trial of tacrolimus, azathioprine and prednisolone with or without basiliximab: two-year follow-up data

Abstract: A total of 192 children and adolescents undergoing renal transplantation were randomly chosen to receive tacrolimus, azathioprine and corticosteroids (TAS, n = 93) or tacrolimus, azathioprine, corticosteroids and two doses of basiliximab (TAS + B, n = 99). Six-month outcome data have previously been reported; this manuscript reports the 2-year data. Complete 2-year data were available on 164 (85.4%) of the original 192 patients. There was a single death in the TAS arm. Kaplan-Meier estimates of survival free o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…46,47 However, a subsequent randomized multicenter European trial showed that, at 2-year follow-up, basiliximab showed no rejection, malignancy, or cardiovascular protection effect among low-immunologic risk pediatric patients on a maintenance regimen of tacrolimus, azathioprine, and steroids. 48 These differences suggest that the immunologic risk of the recipient and composition of the maintenance regimen are important factors to consider when using induction therapy.…”
Section: Induction Immunosuppressionmentioning
confidence: 99%
“…46,47 However, a subsequent randomized multicenter European trial showed that, at 2-year follow-up, basiliximab showed no rejection, malignancy, or cardiovascular protection effect among low-immunologic risk pediatric patients on a maintenance regimen of tacrolimus, azathioprine, and steroids. 48 These differences suggest that the immunologic risk of the recipient and composition of the maintenance regimen are important factors to consider when using induction therapy.…”
Section: Induction Immunosuppressionmentioning
confidence: 99%
“…Although RCTs in mixed populations were identified, none included subgroup analysis by age -providing separate results for children/adolescents and adultsand were therefore excluded from the review (a list of these records can be found in Appendix 2, Table 136). Three RCTs (published in one abstract 72 and seven papers [73][74][75][76][77][78][79] ) met the inclusion criteria.…”
Section: Randomised Control Trialsmentioning
confidence: 99%
“…In summary, three RCTs (published in seven papers [73][74][75][76][77][78][79] and one abstract 72 ) were found eligible and are included in this review (Table 10). • Abstract, n = 332…”
Section: Randomised Control Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion is supplemented with retrospective analyses. In pediatric patients, randomized studies have compared basiliximab with placebo [50] or no induction [51,52] (section 4.2). [18,[31][32][33][34][35][36][37] The efficacy of basiliximab coadministered with corticosteroid-sparing (section 4.1.5) [38][39][40][41][42] or CNI-sparing (section 4.1.6) [43][44][45][46][47] regimens, or its use in diabetic [26,28,48] or elderly [49] patients (section 4.1.7), is also discussed.…”
Section: Therapeutic Efficacymentioning
confidence: 99%